Physiological And Histopathological Analyses Of Silicon Mediated Resistance On Rigidoporus Microporus In Rubber Rootstock Seedlings (Hevea Brasiliensis) - Shaikh Abd Hadi, Shaikh Mohd Hizami (2022)
White root disease (WRD) is the most severe root disease caused by a soil-borne fungus, mainly Rigidoporus microporus. This pathogen destroys the root system, leading to the death of the rubber tree, Hevea brasiliensis Muell. Arg. The periodical application of chemical fungicides (propiconazole) to control this pathogen has caused environmental pollution issues, hazardous to users, and costly. As an option, the application of silicon integrated fertiliser has proven to be successful in managing diseases on rice, apple, chestnut tree and many else. This study aimed to explore the possibility of using soluble silicon to control the incidence of WRD. The variability study and laccase enzyme production test on nine R. microporus isolates from the culture stock were carried out to select three isolates that showed a significant virulence level. In a pathogenicity test, selected isolates of R. microporus were then inoculated on rubber rootstock seedlings to choose the most virulent isolate. Ayer Molek (AM) isolate was indicated to be the most virulent isolate of R. microporus and had been used in further experiments as a primary source of the pathogen. As an alternative element to propiconazole fungicides, studies had been conducted to determine the effect of different types of soluble silicon (silicic acid, sodium meta-silicate, sodium silicate, and calcium silicate) application on R. microporus growth in both in-vitro and in-vivo study.